Central African Economic and Monetary Community (CEMAC) : Staff Report on the Common Policies of Member Countries, and Common Policies in Support of Member Countries Reform Programs-Press Release; Staff Report; and Statement by the Executive Director for the Central African Economic and Monetary Community. (International Monetary Fund, 2021)
The economic shock associated with the COVID-19 pandemic is set to have long-lasting effects on the economic outlook for CEMAC. The pandemic itself seems to be now broadly under control in the region, and the policy response from national and regional authorities, supported by significant emergency financing by the Fund, helped mitigate the initial economic fallout. With lower medium-term oil prices, the outlook projects that CEMAC's fiscal and external adjustments will be slower than previously envisaged, entailing large external financing needs (around Euro 6.6 billion for 2021-23). Gross international reserves will now reach the equivalent of 5 months of imports by 2025 vs. 2022 pre-pandemic, while net foreign assets (NFA) will be below previous expectations. Public debt would remain at elevated levels, albeit on a declining trend after the increase in 2020. This outlook is highly uncertain and contingent on the evolution of the pandemic and its impact on oil prices. Other significant risks include: delayed implementation of the ongoing or a second phase of new Fund-supported programs, difficulties in filling large external financing needs, and a deterioration in the security situation.